Enhanced Antitumor Activity with Combining Effect of mTOR Inhibition and Microtubule Stabilization in Hepatocellular Carcinoma - Qian Zhou; Chi Hang Wong; Cecilia Pik Yuk Lau; Connie Wun Chun Hui; Vivian Wai Yan Lui; Stephen Lam Chan; Winnie Yeo (International Journal of Hepatology)
Mammalian target of rapamycin (mTOR) and the microtubules are shown to be potential targets for treating hepatocellular carcinoma (HCC). PI3K/Akt/mTOR activation is associated with resistance to microtubule inhibitors. Here, we evaluated the antitumor activity by cotargeting of the mTOR (using allosteric mTOR inhibitor everolimus) and the microtubules (using novel microtubule-stabilizing agent patupilone) in HCC models. In vitro studies showed that either targeting mTOR signaling with everolimus or targeting microtubules with patupilone was able to suppress HCC cell growth in a dose-dependent manner. Cotargeting of the mTOR (by everolimus) and the microtubules (by patupilone, at low nM) resulted in enhanced growth inhibition in HCC cells (achieving maximal growth inhibition of 60–87%), demonstrating potent antitumor activity of this combination. In vivo studies showed that everolimus treatment alone for two weeks was able to inhibit the growth of Hep3B xenografts. Strikingly, the everolimus/patupilone combination induced a more significant antitumor activity. Mechanistic study demonstrated that this enhanced antitumor effect was accompanied by marked cell apoptosis induction and antiangiogenic activity, which were more significant than single-agent treatments. Our findings demonstrated that the everolimus/patupilone combination, which had potent antitumor activity, was a potential therapeutic strategy for HCC.